Implementation of modified team-based learning within a problem based learning medical curriculum: a focus group study - Burgess, Annette; Roberts, Chris; Ayton, Tom; Mellis, Craig (BMC medical education, 2018)
Background While Problem Based Learning (PBL) has long been established internationally, Team-based learning (TBL) is a relatively new pedagogy in medical curricula. Both PBL and TBL are designed to facilitate a learner-centred approach, where students, in interactive small groups, use peer-assisted learning to solve authentic, professionally relevant problems. Differences, however, exist between PBL and TBL in terms of preparation requirements, group numbers, learning strategies, and class structure. Although there are many similarities and some differences between PBL and TBL, both rely on constructivist learning theory to engage and motivate students in their learning. The aim of our study was to qualitatively explore students’ perceptions of having their usual PBL classes run in TBL format. Methods In 2014, two iterations in a hybrid PBL curriculum were converted to TBL format, with two PBL groups of 10 students each, being combined to form one TBL class of 20, split into four groups of five students. At the completion of two TBL sessions, all students were invited to attend one of two focus groups, with 14 attending. Thematic analysis was used to code and categorise the data into themes, with constructivist theory used as a conceptual framework to identify recurrent themes. Results Four key themes emerged; guided learning, problem solving, collaborative learning, and critical reflection. Although structured, students were attracted to the active and collaborative approach of TBL. They perceived the key advantages of TBL to include the smaller group size, the preparatory Readiness Assurance Testing process, facilitation by a clinician, an emphasis on basic science concepts, and immediate feedback. The competitiveness of TBL was seen as a spur to learning. These elements motivated students to prepare, promoted peer assisted teaching and learning, and focussed team discussion. An important advantage of PBL over TBL, was the opportunity for adequate clinical reasoning within the problem solving activity. Conclusion Students found their learning experience in TBL and PBL qualitatively different. There were advantages and disadvantages to both. This suggests a hybrid approach utilising the strengths of both methods should be considered for wide scale implementation.